Low-cost IoT and computer vision-based aquaculturemonitoring system - Yamao, Eiriku (2024)
Securing a reliable source of food for the ever-growingpopulation is one of the big challenges for humanity.Demand for aquatic foods will continue to grow andproduction process in aquaculture needs improvement. Alow-cost Internet of Things based system for monitoringhatching and growth of Rainbow trout (Oncorhynchusmykiss) is designed and implemented in a rural area in Peru.Three-layer architecture with sensors and underwatercamera based on raspberry pi, Wi-Fi and satelliteconnection to Internet sends data to cloud services forstorage and analysis. The system reduced drastically themanual and time-consuming monitoring tasks relatedto traditional aquaculture and the data collected will beused to establish optimal growth conditions parametersand future growth predictions.